Primary Intra-operative Embolisation During Urgent Parallel Graft Endovascular Repair in Paravisceral Symptomatic Aortic Pseudoaneurysm - Paolo Spath; Federica Campana; Enrico Gallitto; Chiara Mascoli; Stefania Caputo; Rodolfo Pini; Gianluca Faggioli; Mauro Gargiulo (EJVES Vascular Forum)
Objective: Paravisceral aortic lesions present significant challenges for endovascular treatment. This retrospective analysis of consecutively treated patients from April 2017 to June 2021 aimed to analyse the outcome of primary intra-operative embolisation of aortic complicated pseudoaneurysms and gutter channels during parallel graft (PG) repair of paravisceral symptomatic aortic pseudoaneurysms. Methods: Patients with symptomatic pseudoaneurysms of the paravisceral aorta treated with PGs using chimney or periscope configurations were included. Thoracic endografts were positioned to exclude the aortic lesions. Coil embolisation of both the lesions and gutter channels was performed after graft deployment and prior to ballooning of the stent grafts. The primary endpoints were technical success (defined as exclusion of the pseudoaneurysm, target visceral vessel [TVV] patency, absence of gutter endoleaks) and clinical success (technical success + resolution of symptoms + absence of major adverse events) at 30 days. Secondary endpoints included overall survival, TVV patency, gutter endoleaks, and freedom from re-interventions during follow up. Results: Six patients (four women) were treated for pseudoaneurysm rupture (three cases) and symptomatic aortic pseudoaneurysm (three cases) of the paravisceral aorta. The patients' anatomies were unsuitable for off the shelf devices and patients were all deemed to be at prohibitive surgical risk. A total of 15 TVVs were revascularised (comprising three coeliac arteries, five superior mesenteric arteries, and seven renal arteries) using 10 chimney and five periscope PGs. One coeliac artery was occluded. Seventy coils were deployed to embolise both the aortic ruptures and gutter channels. Both technical and clinical success rates were 100%. The median follow up was 17 months (IQR 5, 35), during which time three patients died due to non-aortic related causes. One coeliac artery (6%) was occluded, and no endoleak evidence was found. Conclusion: Primary intra-operative embolisation during parallel graft endovascular repair of paravisceral symptomatic aortic pseudoaneurysms may be both safe and effective in excluding the pseudoaneurysm when other options are unavailable.